Khazanah Food Enterprise / Ahmad Sayuti Yahya Muhammad… [et al.] - Yahya, Ahmad Sayuti; Suliman, Muhammad Ashraf; Zainal Ahbidin, Muhammad Idzwan; N Hashim, Mohd Afiq; Mohamad Amin, Muhammad Syafiq (2010)
Khazanah Food Industry is the new business entity that formed under the Partnership agreement. The company have been registered in 5th january 2010 with the purpose to introduce and popularized the Malaysian traditional food in the different form that can suit everyone's preference nowadays, and at the same time earning the business profits. Our company will operate the business officially in 5th October 2010. Faced with fast-paced modern life, consumers will continue to seek convenience and simplicity. The demand for the ready-to-eat form food nowadays become increase as the people nowadays tend to buy the product that doesn't provide them complexity, especially for food product. The demand for the junk food is increasing nowadays especially for children and teenagers. But there's an issues that relates the junk food that can effects someone's health as the junk food perceived to have little or no nutritional value, or to products with nutritional value but which also have ingredients considered unhealthy when regularly eaten, or to those considered unhealthy to consume at all. Apart from this issues, we found that this is the opportunity to sell the healthy food in form of snack, that usually represented by the junk food. The existence of our product in the market can give the alternatives to the consumer when it comes to the selection of helthy and delicious snack. Our company is located at bandar Baru perda, Pulau Pinang. We chose Bandar Perda because there is less competitor that will compete will our company in selling the product to the customer. Apart from that, the location is located at the urban area, where the potential buyer will always surround the place. The supplier for the rawa materal situated near to our business location thus reducing the cost on dealing with the process to obtain the raw materials. Other than that, our company also situated near to the distribution area which turn our business' location into the strategic place to produce our product at maximum effort. With the goal to become the well- known brand that become a leader in the snack producing industry, we are striving to satisfied the customer's needs and wants by producing the good quality product that consistent with it's value.